Co‐excitation control of a four‐degree‐of‐freedom magnetic bearing switched reluctance motor based on mathematical models - Zeyuan Liu; Xingcheng Wu; Jun Cai; Yan Yang; Chengzi Liu (IET Electric Power Applications)
Abstract In traditional magnetic bearing motors, the magnetic bearing and the motor are usually driven and controlled separately, resulting in higher controller costs and limiting further expansion of their applications. The author presents a four‐degree‐of‐freedom (4DOF) magnetic bearing switched reluctance motor (MBSRM), consisting of two 8‐pole active radial magnetic bearings (RMBs) and two two‐phase 4/2‐pole switched reluctance motors (SRMs), driven simultaneously by a set of asymmetrical power converters together. Firstly, the structure, winding configuration and co‐excitation working principles of the 4DOF‐MBSRM system are described in detail. Then the radial force formula for an 8‐pole RMB and the torque mathematical model for a 4/2‐pole SRM are briefly derived based on equivalent magnetic circuits, respectively. Furthermore, a co‐excitation control strategy for the 4DOF MBSRM is developed wherein an instantaneous radial force is used to control its rotor shaft levitation, an instantaneous torque is employed for rotational control at low and medium speeds, and an average torque is used for high speed operation. Finally, the good performance of the co‐excitation control for the proposed 4DOF‐MBSRM is proved by simulation analysis.